(untitled) (Applied Biological Research, 2014)
Buckwheat is economically important smaller millet grown primarily for carbohydrate and protein content. In this study, biochemical onstituents of 15 promising genotypes of buckwheat, grown in Sangla region of Himachal Pradesh (India), were analyzed. The moisture, crude protein, carbohydrate, fat, crude fibre and ash contents in genotypesranged from 10.0 to 11.7, 1.7 to 2.5, 1.7 to 2.5, 10.2 to 14.8, 1.8 to 2.9, 7.1 to 9.5 and 62.0 to 66.4%, respectively. The K, P, Mg, Ca, Fe and Zn contents in buckwheat grains varied from 423 to 587.5, 248 to 370.2, 200.5 to 308, 43.7 to 58.03, 3.0 to 4.5 and 2.0 to 3.0 mg 100 g-1, respectively. Based on cumulative grading of nutritionally desirable qualities, the genotypes S-B-216 and Kamru followed by S-B-206 and Chini proved superior cultivars.